2018
DOI: 10.3390/met8060470
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of Surface Softening Behavior for Cu-Bearing Martensitic Steels after Laser Surface Heat Treatment

Abstract: Abstract:The surface hardening and softening behavior of two types of medium carbon martensitic steel (AISI P20-improved and AISI P21) after laser-assisted heat treatment was quantitatively compared. The laser-assisted heat treatment was performed using a high-power diode laser with in situ temperature and laser power control (two-color pyrometer system). For AISI P20-improved steel, the peak hardness value within the hardening zone was approximately 640 HV after laser-assisted heat treatment at a temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…A magnified SEM image (Figure 3b) was obtained and is shown in the red box in Figure 3a. A few nanometer-size particles were observed, and these are known as Cu particles [3,29,30]. Figure 4 shows the XRD profiles of the BM, LH P21, and LN P21.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A magnified SEM image (Figure 3b) was obtained and is shown in the red box in Figure 3a. A few nanometer-size particles were observed, and these are known as Cu particles [3,29,30]. Figure 4 shows the XRD profiles of the BM, LH P21, and LN P21.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate surface treatments can prevent damages to the mold, resulting in an extended mold lifespan. Several studies have investigated the application of surface treatments to mold steels and tool steels in the form of surface heat-treatment [2][3][4][5], nitriding [3,[6][7][8], surface coating and alloying [9][10][11][12], and peening [5,13,14]. Lee et al [2] investigated the laser melting-induced microstructural evolution and surface hardening of SM45C mold steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, to improve the surface wear resistance, Houdková et al attempted the laser-based surface remelting of a thermal-sprayed Co-based alloy [9]. Furthermore, Santhanakrishnan et al, Chun et al and Shariff et al reported on the surface hardening that could be attained by applying laser-based surface heat treatment to tool and plastic molds, as well as railroad steels, respectively [10][11][12]. Hongchao et al also found that laser shock peening enhances the surface hardening behavior and fatigue resistance of titanium (Ti) alloys [13].…”
Section: Introductionmentioning
confidence: 99%
“…The researcher indicated an improvement in the surface mechanical properties such as the micro-hardness and the wear resistance. The laser polishing of different metals has been investigated by several researchers in order to produce a better understanding of the effect of the input processing parameters and to relate them to the modified surface characteristics [34,35]. In order to fill the gap of information available for 316L stainless steel, this paper presents a study of the effect of laser polishing parameters of 316L stainless steel alloy on the resulting surface properties.…”
Section: Introductionmentioning
confidence: 99%